The essential keynotes video collection 2016. (O'Reilly Media, 2016)
"The keynote speakers invited to address the O'Reilly Design Conference represents an unparallelled convocation of some of the leading minds and practitioners in the world of design. This selection of keynotes provides a big-picture perspective on the reach of design and its impact on business and government as well as the challenges that designers face."--Resource description page.